Properties of the structural defects during SiC–crystal–induced crystallization on the solid–liquid interface. (September 2020) - Gao, Yue; Yan, Wanjun; Gao, Tinghong; Chen, Qian; Yang, Wensheng; Xie, Quan; Tian, Zean; Liang, Yongchao; Luo, Jun; Li, Lianxin
Abstract: The high-quality growth of semiconducting single crystals is the basis of the fabrication of high-performance devices. SiC is a promising semiconductor material for fabricating power electronics and radio frequency devices that require crystals to exhibit less crystal defects and high crystal density. In this study, the crystallization induced by the zinc blende crystal structure in SiC crystals on the solid–liquid interface was studied via molecular dynamics simulations. Further, the formation mechanism of the structural defects in SiC crystals is characterized using the radial distribution function, crystallization rate, bond angle distribution function, Voronoi polyhedron, and visualization technology. The results indicate that majority of the atoms on the solid–liquid interface gradually freeze to form crystal structures induced by the nearby stable crystals and that a small number of atoms with relatively high energy randomly diffuse into the liquid regions. Four common defects (vacancy defects, lattice distortion, interstitial atoms, and substitutional defects) are located in different regions in this system. Lattice distortions are commonly formed during the initial stage of crystallization and are decreased during the isothermal process. However, the interstitials and vacancy defects in the crystal are difficult to eliminate during the isothermal process at 3100 K. Highlights: The crystallization induced by the zinc-blende crystal structure in SiC was studied. The different properties of four common defects are investigated by several methods. The effect of defects on crystallization was analyzed. Voronoi polyhedral clusters in solid - liquid systems are analyzed.